Nonrandom occurrence of lymphoid cancer types in 140 families. Issue 9 (2nd September 2017) - Jones, Samantha J.; Voong, Jackson; Thomas, Ruth; English, Amy; Schuetz, Johanna; Slack, Graham W.; Graham, Jinko; Connors, Joseph M.; Brooks-Wilson, Angela
Abstract: We studied 140 families with two or more lymphoid cancers, including non-Hodgkin lymphoma (NHL), Hodgkin lymphoma (HL), chronic lymphocytic leukemia (CLL), and multiple myeloma (MM), for deviation from the population age of onset and lymphoid cancer co-occurrence patterns. Median familial NHL, HL, CLL and MM ages of onset are substantially earlier than comparable population data. NHL, HL and CLL (but not MM) also show earlier age of onset in later generations, known as anticipation. The co-occurrence of lymphoid cancers is significantly different from that expected based on population frequencies ( p  < .0001), and the pattern differs more in families with more affected members ( p  < .0001), suggesting specific lymphoid cancer combinations have a shared genetic basis. These families provide evidence for inherited factors that increase the risk of multiple lymphoid cancers. This study was approved by the BC Cancer Agency – University of British Columbia Clinical Research Ethics Board.